Faktor-Faktor Yang Mempengaruhi Minat Menabung Generasi Milenial Pada Bank Syariah Indonesia (BSI) Kota Banda Aceh - Isthafan Najmi; Cut Delsie Hasrina; Dara Murzalifah (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This research was conducted on the millennial generation at Bank Syariah Indonesia (BSI) Banda Aceh City. The sample in this study was the millennial generation who saved at Bank Syariah Indonesia (BSI) Banda Aceh City as many as 96 respondents. The samples were taken using stratified random sampling technique. Taking into consideration that the population is varied, has different characters, is heterogeneous and the exact number is not yet known. The model used in this research is multiple linear regression analysis. The research results show that trust and service quality simultaneously influence the interest in saving of the millennial generation at Bank Syariah Indonesia (BSI) Banda Aceh City. Trust influences the interest in saving of the millennial generation at Bank Syariah Indonesia (BSI) Banda Aceh City. Service quality influences the interest in saving of the millennial generation at Bank Syariah Indonesia (BSI) Banda Aceh City. The correlation coefficient (R) value is 0.692, which shows that the degree of relationship between the independent variable and the dependent variable is 0.692 or 69.2%, so interest in saving has a close and positive relationship with trust and service quality. The coefficient of determination (R2) is 0.479, meaning that interest in saving can be explained by trust and service quality by 0.479 or 47.9%. Meanwhile, the remaining 52.1% is explained by other variables outside of this research which might influence interest in saving.